Association between Internet use, geographical area and mother tongue in the Peruvian population - Guevara-Tirado, Alberto (2023)
This study aimed to evaluate the association between Internet use with geographical area and mother tongue in the Peruvian population. A descriptive, observational and cross-sectional study was carried out. The information was obtained from the National Household Survey belonging to the National Statistics and Informatics Institute, which included 15,360 people from different regions of the country. The association analysis was carried out using the Chi square test, the intensity of association was carried out with the Phi and Cramer's V correlation tests considering an alpha value of less than 0.05. Data processing and analysis was carried out with the SPSS 25 program. It was found that the Sierra and Selva regions had less Internet use than the Coast and Metropolitan Lima regions (p=0.000). Likewise, the use of native mother tongues was associated with less Internet use than in people whose mother tongue was Spanish (p=0.000), with a low and positive statistical association being found in all cases. In conclusion, Internet use is associated with the geographical area and the type of mother tongue in the Peruvian population.